Economic valuation of Eucalyptus globulus Labill in the DanielHernández district, Pampas -Tayacaja - Gutiérrez Collao, Jairo Edson (2022)
Knowing the timber economic value standing is an important element to achieve efficient management and pursue sustainable development, emphasizing social welfare. For this reason, the research evaluated four plantations of Eucalyptus globulus Labill, distributed in four annexes of the Daniel Hernández district, belonging to the province of Pampas Tayacaja. A total of 77 individuals were inventoried in four installed strips (one strip per plantation) 50 m long and 2 m wide. Quantitative variables (height and diameter of the trees) and qualitative variables (quality of shaft and age of the trees) were evaluated in order to obtain the timber economic value of the four strips. As a result, it was reported that 18,2 % of the trees are more than 40 cm in diameter and are in a usable situation; However, 79,2 % have stem 2 and 3 qualities, which implies that silvicultural treatments should be performed or applied. Likewise, the total timber economic value of the four girdles (considering shaft quality and age) was S /. 7 473,18.